(untitled) (Biuletyn Kryminologiczny, 2021)
The article presents various definitions of prevention, which are described through five levels: semantic, legal, institutional, practical and teleological. The first part of the article is dedicated to the general understanding of prevention and the second is about the prevention of human trafficking for sexual exploitation. This article is based on two sources: international legal standards and academic literature. W artykule przedstawione zostały różne definicje prewencji, które można opisać za pomocą pięciu wymiarów: semantycznym, prawnym, instytucjonalnym, praktyczny i teleologicznym. W artykule omówiona jest prewencja na poziomie ogólnym oraz jeden z jej przykładów – prewencji handlu ludźmi w celach seksualnych. Artykuł powstał na podstawie dwóch źródeł: międzynarodowych aktów prawnych oraz literatury naukowej z różnych dziedzin.